Pengaruh Gaji, Insentif, dan Bonus terhadap Kepuasan Kerja Mitra Pengemudi Grab Car PT. Solusi Transportasi Indonesia Cabang Kota Manado - Thanan, Rizki Reinaldi; Pio, Riane Johnly; Kalangi, Johny A. F. (Sam Ratulangi University, 2021)
Rewards are one of the factors that affect various human resource activities at every company. The purpose of this research is to determine the effect of salary, incentives, and bonuses based on job satisfaction of Grab Car driver branch PT. Solusi Transportasi Indonesia at Manado City. The value purpose for this research was doing a survey to Grab Car drivers at Manado City as a sample within 100 respondents. The Regression Analysis is the method that was used for this research and the result found as partial that salaries, incentives, and bonuses have an impact on job satisfaction. The multiple regression research also found that salaries, incentives, and bonuses have a big impact on job satisfaction. The elements of reward such as salaries, incentives, and bonuses have become the very crucial parts of job satisfaction. Therefore, the company management should give serious attention to implementing it, to avoid decreasing the impact that Grab Car driver for job satisfaction to decreased incentives and bonuses.